Function of protein ubiquitination and SUMOylation in regulating flowering time of plants: A review - Zhang Xiaolian; Zhang Jishun; Zou Jie; Zhao Jiehong; Ren Xueliang (浙江大学学报. 农业与生命科学版)
Flowering is an important process in the life cycle of plants to complete the transition from vegetative growth to reproductive growth and to ensure the yield and production of next generation. Therefore, flowering time is a considerable agronomic trait in plants. There are many factors influencing flowering time, including internal factors, such as hormone and carbohydrate, and environmental factors, such as light and temperature. Different plant species have evolved complicated networks to modulate the flowering time accurately in response to environmental cues and endogenous signals. Studies in Arabidopsis have led to the identification of the major flowering pathways: the photoperiod pathway, the vernalization pathway, the ambient temperature pathway, the autonomous pathway, the gibberellic acid (GA) pathway and the age pathway. Multiple flowering regulatory pathways converge to control the activation of floral integrator genes, such as FT and SOC1. The flowering time genes and their regulation pathways are highly conserved in Arabidopsis, rice and other higher plants. The key regulators of floral transition have been studied extensively in plants.As aspects of protein post-translational modifications, the ubiquitin/26S proteasome pathway and SUMOylation play key roles in almost every aspect of growth and development for plants, including the regulation of plant flowering time. Protein stability, degradation, location, and interaction with other proteins were also regulated under these pathways. The ubiquitination pathway usually contains three steps. First, the E1 (ubiquitin activating enzyme) forms a thioester bond with the C terminus of the 76-amino acid ubiquitin protein. Second, the activated ubiquitin is transferred to an E2 (ubiquitin conjugating enzyme) . Third, with the help of the E3 ligase, ubiquitin is transferred to the substrate by E2, and at last forms a ubiquitinated substrate protein. These processes are then repeated to attach new ubiquitin molecules to the substrate protein, and polyubiquitination has been shown to be essential for recognition and degradation of the substrate by the 26S proteasome. The polyubiquitin chain can be disassembled by the DUB (deubiquitinating enzyme) to release ubiquitin moieties. The process of SUMOylation is similar with ubiquitination except for some small differences.Flowering time appears to be regulated by modulation of protein stability and degradation mediated by ubiquitination and SUMOylation. According to the study of Arabidopsis genome, there are more than 1 400 genes encoding components of the ubiquitin/26S proteasome pathway. Many of these genes mediate the degradation of the key proteins in the flowering pathways, such as CO protein. In this paper, recent advance on mechanisms of ubiquitination and SUMOylation regulating flowering time was discussed. First, the functions of the ubiquitination and related genes in the photoperiod pathway, as a major part of this review, were described in details. Furthermore, ubiquitination taking part in photoreceptor degradation, circadian clock regulation, and the modulation of the downstream gene expression and protein stability was discussed. The second part was that the ubiquitination involved in the temperature pathways including the vernalization pathway, the ambient temperature pathway, and the short-term cold stress pathway. The function of DELLA proteins was discussed in the third part. In the fourth part, the roles of SUMOylation and its related genes in the flowering regulation pathways were briefly summarized. At last, some suggestions were given on the methods to study the function mechanisms of ubiquitination and SUMOylation on flowering time. We hope that this review will provide a foundation for a better understanding of the role of protein post-translational modifications in flowering pathways.